Work-related musculoskeletal disorders among information technology professionals in Riyadh, Saudi Arabia - Ahmad H. Alghadir; Salman Khalid; Zaheen Ahmed Iqbal (Nofer Institute of Occupational Medicine, 2022)
Background This study was done to see the prevalence of work-related musculoskeletal disorders among information technology (IT) professionals in Saudi Arabia, the risk factors associated with them, their consequences, and to propose some preventive measures. Material and Methods A self-administered online questionnaire that included questions on the demographic data, job nature, medical history, work-related pain after joining information technology profession and distribution and severity of pain was sent to 250 information technology professionals working in Saudi Arabia. Results Out of 250, 202 (81%) IT professionals participated in the study. At least 62 (32%) reported that they have developed some type of musculoskeletal pain after joining their profession and 38 (61%) respondents further reported that it was so severe that they had to seek some sort of treatment for their pain. On the Visual Analog Scale ranging 0-10, 14 (23%) respondents reported that their worst ever pain was >7. Despite lower representation 67% of the females reported to develop work-related pain. Conclusions Development of work-related musculoskeletal pain among information technology professionals has been shown to affect their activities of daily living. It may even force them to change their work setting or reduce working hours. Information technology sector has rapidly grown in Saudi Arabia in the recent times and there is no data on the incidence or prevalence of such disorders among them. Role of ergonomics and counseling should be emphasized during their training that help them work effectively and efficiently. A similar large-scale study should be conducted to see the effect of lifestyle related to COVID-19 on the lives of working population especially IT professionals. Med Pr. 2022;73(5):397-406